1993
DOI: 10.1111/j.1365-2621.1993.tb03202.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Protein Texturized Products of Defatted Soy Flour, Corn Starch and Beef: Shelf‐Life, Physical and Sensory Properties

Abstract: Selected mixes consisting of Bf [high-beef (29%) low-fat (2.96%)], bf [low-beef (20%) low-fat] and BF [high-beef high-fat (S%)] which incorporated raw beef, defatted soy flour, and corn starch were extruded in a single-screw extruder. The products had no flavor additives and trained sensory panelists detected hay-like, beany or grainy flavors. Bf extrudate was more expanded than BF extrudate and rated least hard by the sensory panel, whereas bf extrudate was least susceptible to lipid oxidation. Bf and bf extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…[35][36][37] High starch content of corn and low fat level have also been reported to lead to extrudates with high WAI. [38] The effect of pigeon pea flour addition to cassava flour on the physicochemical quality of extrudates was investigated by Rampersad et al, [39] who found out that products with added pigeon pea flour had higher WAI.…”
Section: Functional Propertiesmentioning
confidence: 99%
“…[35][36][37] High starch content of corn and low fat level have also been reported to lead to extrudates with high WAI. [38] The effect of pigeon pea flour addition to cassava flour on the physicochemical quality of extrudates was investigated by Rampersad et al, [39] who found out that products with added pigeon pea flour had higher WAI.…”
Section: Functional Propertiesmentioning
confidence: 99%
“…The L* value could be the most important because it shows the sausage losing its white tone and becoming darker, which could affect its acceptance among consumers. A falling L* value could be related to lipid oxidation and the production of malondialdehyde, which was higher than the meat's dark color (Park, Rhee, Kim, & Rhee, 1993). Furthermore, some brown coloring could be due to oxidation from light and oxygen, as the light separates nitric oxide from the hemo group of hemoglobin and this, in turn, is oxidized by air (Akesowan, 2008;Gregg, Claus, Hackney, & Marriot, 1993).…”
Section: Color Evaluationmentioning
confidence: 99%
“…They reported that when starch was used in large quantity, water absorption index of extrudates increased due to increased starch gelatinization. Park et al, (1993) also reported that high starch and low fat level resulted in higher water absorption index of products. Water solubility index significantly decreased from control to chicken meat incorporated seasoning fryums.…”
Section: Physico-chemical Characteristicsmentioning
confidence: 93%